Causal Effects of the Fed's Large-Scale Asset Purchases on Firms' Capital Structure - Andrea Nocera; M. Hashem Pesaran (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper investigates the short- and long-term impacts of the Federal Reserve's large-scale asset purchases (LSAPs) on the capital structure of U.S. non-financial firms. To isolate the effects of LSAPs from the impact of concurrent macroeconomic conditions, we exploit cross-industry variations in the ability of firms therein to raise external funds without exhausting their debt capacity. We show that firms' responses to LSAPs strongly depend on the financing decisions of other peers in the same industry. The higher the proportion of firms without high debt burdens in an industry, the stronger the response of firms within the industry to the Fed's asset purchases. Overall, our results show that LSAPs facilitated firms' access to debt financing and that the impacts of LSAPs on firms' capital structure are likely to be long-lasting.
Keywords: C32; E44; E52; E58; 330; capital structure; identification; interactive effects; leverage; quantitative easing; unconventional monetary policy